2013
DOI: 10.1371/journal.pone.0064457
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Acute Myocardial Infarction Hospitalization Rates for US States in the CDC Tracking Network

Abstract: ObjectivesWe examined temporal trends, spatial variation, and gender differences in rates of hospitalization due to acute myocardial infarction.MethodsWe used data from the Centers for Disease Control National Environmental Public Health Tracking Network to evaluate temporal trends, geographic variation, and gender differences in 20 Environmental Public Health Tracking Network states from 2000 to 2008. A longitudinal linear mixed effects model was fitted to the acute myocardial infarction hospitalization rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 13 publications
(11 reference statements)
4
19
0
Order By: Relevance
“…However, while aging does tend to increase the prevalence of IHD, we estimated that prevalence rates for IHD will actually decline during 2015-2024. This finding is consistent with long-standing trends toward decreasing prevalence of acute coronary syndrome across all age groups in the U.S. population (Krumholz, Normand, & Wang, 2014;Talbott et al, 2013). However, this decline largely represents an extrapolation of recent declines in the prevalence of IHD noted in MEPS; this finding assumes that the previous trend toward reduced prevalence of IHD will continue.…”
Section: Projected Health Care Needs Of Veteranssupporting
confidence: 83%
“…However, while aging does tend to increase the prevalence of IHD, we estimated that prevalence rates for IHD will actually decline during 2015-2024. This finding is consistent with long-standing trends toward decreasing prevalence of acute coronary syndrome across all age groups in the U.S. population (Krumholz, Normand, & Wang, 2014;Talbott et al, 2013). However, this decline largely represents an extrapolation of recent declines in the prevalence of IHD noted in MEPS; this finding assumes that the previous trend toward reduced prevalence of IHD will continue.…”
Section: Projected Health Care Needs Of Veteranssupporting
confidence: 83%
“…This implies that only some racial and sex differences were attributable to age and period effects, and some disparities still persisted, although they narrowed in adjusted analyses. Another study using the CDC data reported that the male-female ratio for AMI hospitalization rates remained constant at 2:1 from 2000 to 2008 [21]. Second, we found a marked increase in the utilization of revascularization among all patient cohorts over time.…”
Section: Discussionsupporting
confidence: 48%
“…Chen and Krumholz examined trends in AMI hospitalization among Medicare beneficiaries between 2002 and 2007 and noted an approximately 20% decline in hospitalization rates [20]; they also found evidence of higher AMI hospitalization rates among men compared to women and white men as compared to black men. Similarly, Talbott et al reported a 20% decline in AMI hospitalization rates using the Centers for Disease Control (CDC) data [21]. Alternatively, data show declines in cardiovascular disease mortality over time without corresponding reductions in AMI hospitalization rates [22].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They have conducted a descriptive analysis of temporal trends, spatial variation, and gender differences in age-adjusted rates of hospitalizations for AMI using data currently available on the Tracking Network (Talbott et al, 2013). Results showed a 20% decrease in AMI hospitalizations from 2000 to 2008 for most Tracking states, higher rates in the New England/Mid-Atlantic region, and two-fold higher rates among men than women.…”
Section: Continued Collaboration With Academia To Address Challengesmentioning
confidence: 99%